The Effect of Transformational Leadership, School Culture, and Work Motivation on the Performance of State High School Teachers in Cirebon City - Rahmawati, Moza; Ramadani, Suci; Putri Sabrina, Adin; Hartono, Edy (LPPM of NAROTAMA UNIVERSITY, 2024)
Purpose: The objective of this research is to examine how the performance of high school teachers in Cirebon City is affected by school culture, work motivation, and transformational leadership. Design/Methodology/Approach: A quantitative approach was used in this research. 535 teachers in state high schools in Cirebon City comprised the population of this study. Simple random sampling was the sampling method used, where 84.25 or 84 respondents were obtained, and data collection samples were collected using a questionnaire, with the sample size determined using the Slovin formula. Findings: The findings indicate the relationship between work motivation, school culture, and transformational leadership with teacher performance. Limitations/Research Implications: The effect of work motivation, school culture, and transformational leadership on teacher performance is the main focus of this research. Practical Implications: Based on the study results, it is evident that teacher performance is simultaneously affected by all three variables - transformational leadership, school culture, and work motivation - both directly and indirectly. The performance of high school teachers in Cirebon City is collectively affected (simultaneously) by school culture, work motivation, and transformational leadership, in accordance with the study's findings on these factors. Originality/Value: This paper is original Paper Type: Research Paper